Mitotane treatment in patients with adrenocortical cancer causes central hypothyroidism. (18th August 2015) - Russo, Marco; Scollo, Claudia; Pellegriti, Gabriella; Cotta, Oana Ruxandra; Squatrito, Sebastiano; Frasca, Francesco; Cannavò, Salvatore; Gullo, Damiano
Summary: Introduction: Mitotane, a steroidogenesis inhibitor with adrenolytic properties used to treat adrenocortical cancer (ACC), can affect thyroid function. A reduction of FT4 levels with normal FT3 and TSH has been described in these patients. Using an in vitro murine model, the secretory capacity of thyrotrophic cells has been shown to be inhibited by mitotane. Objective: To investigate the pathogenesis of thyroid abnormalities in mitotane‐treated patients with ACC. Patients and Methods: In five female patients with ACC (median age 47; range 31–65) treated with mitotane (dosage 1·5 g/day; 1·0–3·0), we analysed the pattern of TSH and thyroid function index (FT4, FT3 and FT3/FT4 ratio) compared to an age‐ and gender‐matched control group. The in vivo secretory activity of the thyrotrophic cells was evaluated using a standard TRH test (200 μg), and the response was compared to both a group of age‐matched female controls ( n  = 10) and central hypothyroid patients ( n  = 10). Results: Basal TSH (median 1·54 mU/l; range 1·20–2·17) was normal and scattered around our median reference value, FT3 levels (median 3·80 pmol/l; 3·30–4·29) were normal but below the median reference value of 4·37 pmol/l and FT4 levels were below the normal range in all patients (median 8·40 pmol/l; 7·6–9·9). FT3/FT4 ratio was in the upper range in 4 patients and higher than normal in one patient. A blunted TSH response to TRH was observed in mitotane‐treated patients. ΔTSH (absolute TSH response, peak TSH minus basal TSH) was 3·65 (range 3·53–5·26), 12·37 (range 7·55–19·97) and 1·32 mU/l (range 0·52–4·66) in mitotane‐treated patients, controls and central hypothyroid patients, respectively. PRL secretion was normal. Conclusions: Mitotane‐treated patients with ACC showed low FT4, normal FT3 and TSH and impaired TSH response to TRH, characteristic of central hypothyroidism. Furthermore, the elevated FT3/FT4 ratio of these subjects reflects an enhanced T4 to T3 conversion rate, a compensatory mechanism characteristic of thyroid function changes observed in hypothyroid conditions. This finding thus confirms in vitro studies and may have a therapeutic implication for treatment with thyroid hormones, as suggested by current guidelines for this specific condition.